RODA - Repository of Authentic Digital Objects - Faria, Luís (2007)
The National Archive of Portugal (IAN/TT) doesn't currently have the needed infrastructures to support the processes of ingestion and management of digital objects produced by the public administration (PA). The eGovernment initiatives establish the need of information and communication technologies support, to improve the efficiency, productivity and quality of their public services. In this scenario, it is clear that the number of digital objects produced by these institutions will grow, and that their legal value and authenticity should be assured. Furthermore, these digital objects will be the testimony of public organizations activity and will constitute the Portuguese social and patrimonial memory. On that account, the IAN/TT should undertake the endeavor of developing processes, tools and resources capable of answering the needs of the public administration institutions in terms of preservation of the digital items being produced. The goal of this project is to provide technical solutions to digital preservation, applicable to a national archive. A prototype is expected to be produced, which will be the basis for the development of a fully functional solution, capable of ingesting and managing digital objects.